Alimentação como direito social: trajetórias e práticas do comer no Sesc SP (1947-2000) - Fernandes, Alan Dias (2023)
This dissertation explores the historical aspects about nutrition and the public policies related to it in Brazil, as well as the way in which Sesc SP has addressed and responds to the social demands related to nutrition. The long-lasting performance of Sesc SP in the field of nutrition reflects historical assimilations and social practices, therefore the researched theme is justified through the recognition, the relevance, and the social and cultural impacts of this social institution. The method adopted starts from a historical perspective, based on bibliographic surveys on nutrition, nourishment, and education. The documental research in the Sesc Memórias of Sesc SP collection analyzed the annual reports of the institution between the years 1947 and 2000, among other documents, which made it possible to analyze Sesc SP's actions regarding nutrition. The research contemplated the creation of the "Restaurante do Comerciário Alcântara Machado" and ended, as a chronological option, with the appearance and elaboration of the so-called "Comedorias", the current concept of nutrition for the institution. As a result, it is hoped that this research will expand and contribute, through its experiences, to the institution itself and to environments such as public education and educational and cultural spaces. In a multidisciplinary way, this research points to nutrition as a universal human right, as a social and cultural practice, considering it in an integral way. Furthermore, by considering the aspects and contexts linked to nutritional policies in Brazil and food education, the research indicated a critical perspective of food and nutrition education as a possible path to food autonomy